ONLINE HOMEWORK SYSTEMS IN CALCULUS - Atanasov, Risto (Matematichki Bilten, 2016)
We will discuss the effectiveness of online homework in Calculus courses. Specifically, we will discuss the use of WeBWorK – an open-source online homework system supported by the Mathematical Association of America and the National Science Foundation. We will confer practices for implementing WeBWorK homework for Calculus and discuss student learning using this online homework system.